Este România o ţară de asistaţi social? - Arpinte, Daniel (Calitatea Vieții, 2019)
The article aims at analysing the last amendments to the Minimum Income Guaranteed Law, the 29th since its enacting, from the perspective of the lawmaker's motivation for the introduced changes and the potential impact for the inclusion of social aid recipients. The main findings of analysis of the available data about meanstested benefits contradict the reasons for the change of law, the social aid system being undersized and providing inadequate and insufficient protection for those living in extreme poverty. The article analysis also the means-tested benefits system, the available data revealing a strong relation between the level of the economic development and the proportion of the social aid beneficiaries in total population. Another important aspect examined in the article is the low share of the expenditure for family, child and social exclusion, with one of the lowest levels for Romania, while the overall social expenditures being at half of EU28 average. The conclusions show that the law changes are based on misleading assumptions, being ignored the real priorities such as the diversifying the types of support which might increase the social inclusion of social aid beneficiaries or providing sufficient support for a decent living.